2018
DOI: 10.1111/petr.13127
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal treatment including tandem high‐dose chemotherapy and autologous stem cell transplantation in children with anaplastic ependymomas

Abstract: In this study, we evaluated the results of multimodal treatment that included tandem HDCT/auto-SCT in children with anaplastic ependymomas. Fourteen patients with anaplastic ependymomas were enrolled from 2006 to 2014. Six cycles of induction chemotherapy were administered to all patients before they underwent tandem HDCT/auto-SCT. Patients who were older than 3 years of age were administered RT after two cycles of induction chemotherapy. In patients under 3 years of age, RT was either omitted or delayed until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For those >3 years old, after primary surgery, radiotherapy was sandwiched between chemotherapy and followed by HDC with ASCT. The 5-year OS and EFS rates were 85.1% ± 9.7% and 50.0% ± 13.4%, respectively 9. Our experience with HDC and ASCT in University Malaya Medical Center (UMMC) did not show promising result in infants and young children with ependymoma.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…For those >3 years old, after primary surgery, radiotherapy was sandwiched between chemotherapy and followed by HDC with ASCT. The 5-year OS and EFS rates were 85.1% ± 9.7% and 50.0% ± 13.4%, respectively 9. Our experience with HDC and ASCT in University Malaya Medical Center (UMMC) did not show promising result in infants and young children with ependymoma.…”
mentioning
confidence: 65%
“…et al8 concluded that this approach seems to be ineffective in infratentorial ependymoma in the absence of radiotherapy and should be investigated further in supratentorial ependymoma with residual disease following surgery.Given this, we have read with interest the study by Lee et al,9 who described the favorable outcome with multimodal treatment including tandem HDC with ASCT and radiotherapy in children with anaplastic ependymomas. Two treatment regimens were used in their study.…”
mentioning
confidence: 99%